Effects of thinner exposure on the expression pattern of neural cell adhesion molecules, level of lipid peroxidation in the brain and cognitive function in rats - Baydas, G; Ozveren, F; Tuzcu, M; Yasar, A (Elsevier, 2005)
Thinner containing 60-70% toluene is a neurotoxic mixture, which is widely used as an aromatic industrial solvent. This product has been shown to cause functional and structural changes in the central nervous system. Thinner generates reactive oxygen species and the toxic effects relating to these reactants. We have investigated the effect of exposure to high concentrations (3000 ppm) of thinner for 45 days (1 day) on cognitive function and the levels of neural cell adhesion molecules (NCAM) and lipid peroxidation products in the hippocampus, cortex and cerebellum of rats. Thinner exposure caused a significant increase in lipid peroxidation products (malondialdehyde and 4hydroxyalkenals) in all brain regions. Levels of NCAM 140 and NCAM 180 kDa were significantly decreased in the hippocampus and cortex of the thinner-exposed group. Furthermore, thinner-exposed rats showed cognitive deficits in passive avoidance and Morris water maze tasks. These cognitive deficits may be due to both elevated oxidative stress and changes in synaptic plasticity. Almost all studied parameters were reversed in animals which were allowed to recover from thinner inhalation, suggesting that the effects of exposure to thinner, at least for I h/day for 45 days, are reversible. (c) 2005 Elsevier B.V. All rights reserved.
Keywords: thinner; learning; memory; NCAM; (Rat)